Investigation of exercise-related leg pain, fear of pain, kinesiophobia, and injury anxiety in athletes - Bingöl, E.; Tiryaki, K.; Tümtürk, I.; Özden, F. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study aimed to investigate the relationship between exercise-induced leg pain, fear of pain, kinesiophobia and injury anxiety in amateur and professional athletes. Secondarily, the present study also aimed to investigate the relationship between women or men athletes and individual or team sports.